2011
DOI: 10.5194/amtd-4-5857-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Autofluorescence of atmospheric bioaerosols – fluorescent biomolecules and potential interferences

Abstract: Primary biological aerosol particles (PBAP) are an important subset of air particulate matter with a substantial contribution to the organic aerosol fraction and potentially strong effects on public health and climate. Recent progress has been made in PBAP quantification by utilizing real-time bioaerosol detectors based on the principle that specific organic molecules of biological origin such as proteins, coenzymes, cell wall compounds and pigments exhibit intrinsic fluorescence. The properties of many fluoro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 228 publications
(162 reference statements)
2
23
0
Order By: Relevance
“…Fluorescence spectra were recorded on a LS 45 luminescence spectrometer (PerkinElmer, Inc., Waltham, MA, USA). A detailed instrument description is given in Poḧlker et al 31 Samples were analyzed in a 10 × 10 × 40 mm UV quartz cuvette (Hellma Analytics, Mullheim, Germany). The photomultiplier tube detector voltage was 600 V. Excitation wavelengths were 240−400 nm (10 nm increments), whereas emission was recorded from 280 to 560 nm (0.5 nm increments).…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence spectra were recorded on a LS 45 luminescence spectrometer (PerkinElmer, Inc., Waltham, MA, USA). A detailed instrument description is given in Poḧlker et al 31 Samples were analyzed in a 10 × 10 × 40 mm UV quartz cuvette (Hellma Analytics, Mullheim, Germany). The photomultiplier tube detector voltage was 600 V. Excitation wavelengths were 240−400 nm (10 nm increments), whereas emission was recorded from 280 to 560 nm (0.5 nm increments).…”
Section: Introductionmentioning
confidence: 99%
“…Light at 488 nm is known to excite relatively strong fluorescence in bacteria and tree leaves [8]. Sporopollenin in pollens and fungal spores is reported to fluoresce in the 400-650 nm range with high fluorescence intensity when excited at 300-550 nm [56,57]. Flavins are likely to be a main contributor to the fluorescence in the 500-580 nm range in bacteria, but probably contribute a much smaller fraction of the fluorescence in this range in pollens and fungal spores because they have many other fluorescent molecules [56,57].…”
Section: Comparison Of Ptrs Spectra Of Three Pollens and One Type Of mentioning
confidence: 99%
“…Fluorescence spectra or fluorescence band (single or multiple) intensity measurement can be utilized to discriminate bioaerosols from other aerosols (P€ ohlker et al 2012;Pan 2015). Fluorescence-based online bioaerosol instruments, such as BioScout, WIBS, and UV-APS, have been used in various environments, but it is really challenging to classify different types of bioaerosols with these instruments (Gabey et al 2010;Huffman et al 2010;Saari et al 2014).…”
Section: Lif Spectra Of Microbial Particlesmentioning
confidence: 99%
“…It is an effective method for detecting biological molecules such as tryptophan, NAD(P)H, and flavins that are typically present in microbial cells (Lakowicz 2009). LIF enables the differentiation of bioaerosols from other airborne particles through their fluorescence ability (P€ ohlker et al 2012;Hill et al 2013). Saari et al (2013) demonstrated that bacterial and fungal spores may be distinguished from each other through their dissimilar fluorescence spectra.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation